Patient Flow Analysis in Resource-Limited Settings: A Practical Tutorial and Case Study - Dixon, Cinnamon A (Glob Health Sci Pract, 2015)
Patient flow analysis (PFA), a simple quality improvement tool to identify patient flow patterns, can be used in resource-limited settings to inform service delivery improvements. A PFA at a Ghanaian hospital found that personnel constraints and a mismatch between staffing and patient arrival surges led to long wait and total attendance times. The median time from arrival to first-provider contact was 4.6 hours.